Concurrent tolerance charting for component and assembly using ?modified tree? approach - Ngoi, B. K. A.; Min, O. J. (International journal of advanced manufacturing technology, 1997)
The interaction between components in an assembly plays a major role in the performance and reliability of the assembly. However, in conventional design, the dimensions and tolerances of components are usually assigned intuitively to satisfy design constraints. Tolerance analysis is then performed to determine the critical tolerance accumulation that results from the assembly. The tolerances are then modified so that the interaction requirements are satisfied. This approach relies on the experience of the designers and the results may not be an optimum.This paper presents a direct method to determine the working dimensions and tolerances of components that allows control of the assembly interaction. The model is easy to construct and it provides a clear picture of the entire process and assembly links. Using the model, a set of linear equations is formulated directly based on the design constraints and interaction requirements. With appropriate constraints derived in terms of the process capabilities, the desired working dimensions and tolerances can be determined using LINDO, software for solving the linear programming problem. This approach allows the working dimensions and tolerances of all components in an assembly to be determined concurrently.